An Untapped Market: The Potential of Tourism in Iran - rahimi, golnaz (2011)
Tourism industry is one of the largest and most important sectors of economic development in the world, for both developing and developed countries. According to Tourism 2020 Vision, the international arrivals are expected to even reach over 1.56 billion by the year 2020. This research will evaluate Iran’s potential in the tourism industry and especially cultural tourism development and tries to compare it with Turkey (as Iran’s main competition in the Middle East) because of their regional proximities and similarities in culture, religion and attractions. Scientific research shows that increasing international tourism arrivals is a way to generate more revenue than oil and development of tourism is an alternative to oil based economy. The main goal of this research is to evaluate the accelerating and decelerating factors in tourism development in Iran (by comparison with Turkey). The analysis is based on electronic data and the questionnaires that were answered by foreigner tourists in Iran. After inquiry and evaluation of tourism resources in Iran, we can conclude that Iran and Turkey both have almost the same resources with similar culture and tradition but however, Turkey attract more tourists than Iran and they do it by highlighting some of their ancient tradition and also by organizing huge number of festivals each year and providing facilities such as resort hotels and also good hospitality and transportation which have a huge impact on the number of their visitors. But as for Iran, the poor condition of the museums and historical sites, the badly damaged infrastructure and the shortage of investments especially for research are some of the highlights of the weaknesses of their tourism industry.